Clinical utility of ingenol mebutate in the management of actinic keratosis: perspectives from clinical practice - Skroza N; Bernardini N; Proietti I; Potenza C (Dove Medical Press, 2018)
Nevena Skroza, Nicoletta Bernardini, Ilaria Proietti, Concetta Potenza Dermatology Unit “Daniele Innocenzi”, Department of Medical-Surgical Sciences and Bio-Technologies, Sapienza University of Rome, Fiorini Hospital, Polo Pontino, 04019 Terracina, Italy Abstract: Actinic keratoses (AKs) are epidermal cutaneous neoplasia observed predominantly in middle-aged and older subjects with mainly photo type I and photo type II on sun-exposed surfaces as a result of DNA damage. AKs have historically been characterized as being “precancerous”; however, now it is considered by many authors a carcinoma in situ that can persist or progress to invasive squamous cell carcinoma (SCC) with metastatic potential. Despite the advances in the recognition of typical clinic, dermoscopic and histologic patterns, currently it is not yet possible to predict which AKs will progress to SCC. For this reason, early diagnosis and effective therapy are recommended based on cost/risk/benefit analysis. Current treatment consists of lesion-directed or field-directed therapies or a combination of both. Among the topical field therapies, ingenol mebutate stands out for its therapeutic efficacy, both as directed lesion therapy and as field directed therapy. The aim of this review is to demonstrate the utility of ingenol mebutate in the management of AK in daily clinical practice and to highlight data from real world in order to confirm evidence from pivotal studies. In order to explore clinical data from real world, PubMed searches were performed with the search terms “clinical data ingenol mebutate” and “real world ingenol mebutate”. The hits were examined for relevant articles using defaults criteria. The timeframe for the sample search started from the first publication on this topic in 2008 up to now. A total of 23 articles were found using the keywords specified above. The overview points out a low number of real-life studies on the effectiveness and tolerability of this novel treatment due to short period of clinical experience for its recent approval. Further real-life studies are required in order to better identify the efficacy, safety and adherence of the drug on a larger population. Keywords: ingenol mebutate, actinic keratosis, field cancerization, real world, photodamage, novel treatment